2010
DOI: 10.1590/s0100-83582010000100014
|View full text |Cite
|
Sign up to set email alerts
|

Impacto do glyphosate associado com endossulfan e tebuconazole sobre microrganismos endossimbiontes da soja

Abstract: RESUMO -Objetivou-se neste trabalho avaliar o efeito do glyphosate, em aplicação sequencial, e da sua interação com endossulfan + tebuconazole na colonização micorrízica, na nodulação e nos teores de fósforo e nitrogênio foliar em plantas de soja. O experimento foi conduzido a campo em Argissolo Vermelho-Amarelo câmbico, no ano agrícola de 2007/08. Foram avaliados dez tratamentos em em esquema de parcelas subdivididas, no delineamento de blocos casualizados, com quatro repetições. Nas parcelas, avaliou-se o ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 21 publications
0
11
0
6
Order By: Relevance
“…Dvoranen et al (2008) using glyphosate in different application kinds observed no influence of DMPA in soybean cultivars BRS 245 RR and BRS 247 RR, which is consistent with the expected selectivity of herbicides in relation to soybeans. In contrast, Reis et al (2010) found negative effects of glyphosate on DMAP of a soybean cultivar BRS Favorite RR in a sequential and single application. It is suggested that the effects of glyphosate on DMAP are depending on the cultivar; although they are considered resistant to the product, there are variations in the level of resistance.…”
Section: Palavras-chave: Bradyrhizobium Roundup Glycine Maxmentioning
confidence: 76%
See 2 more Smart Citations
“…Dvoranen et al (2008) using glyphosate in different application kinds observed no influence of DMPA in soybean cultivars BRS 245 RR and BRS 247 RR, which is consistent with the expected selectivity of herbicides in relation to soybeans. In contrast, Reis et al (2010) found negative effects of glyphosate on DMAP of a soybean cultivar BRS Favorite RR in a sequential and single application. It is suggested that the effects of glyphosate on DMAP are depending on the cultivar; although they are considered resistant to the product, there are variations in the level of resistance.…”
Section: Palavras-chave: Bradyrhizobium Roundup Glycine Maxmentioning
confidence: 76%
“…These damages are reported in nodulation tests made in the laboratory where the herbicide is applied directly on the strains, as in field conditions (MALTY; SIQUEIRA; MOREIRA, 2006;BOHM ROMBALDI, 2010;REIS et al, 2010). These losses are due to the interference of the herbicide in the microsymbionts metabolism, in host plant or both.…”
Section: Palavras-chave: Bradyrhizobium Roundup Glycine Maxmentioning
confidence: 99%
See 1 more Smart Citation
“…Diedhiou et al (2004) observaram que a azoxistrobina + kresoxim-metil não afeta a colonização de Glomus coronatum Giovannetti em milho quando respeitada a dose recomendada em pulverização foliar. Reis et al (2010) testaram o tebuconazol associado ao endossulfan e glifosate e concluíram que não houve prejuízo à colonização micorrízica em soja. Entretanto, efeito de restrição sobre a colonização micorrízica em ervilha e grão de bico com a aplicação de trifloxistrobina foi constatado por Jin et al (2013).…”
Section: Resultsunclassified
“…O tebuconazol é mencionado como não impactante a este tipo de endófito (Burrows & Ahmed, 2007;Reis et al, 2010), o que pode ter atenuado o estresse quando aplicado em mistura. Schalamuk et al (2014) verificaram aumento na densidade de esporos e arbúsculos de FMAs a partir da aplicação de tebuconazol + trifloxistrobina no controle da septoriose no trigo.…”
Section: Resultsunclassified